2002
DOI: 10.1136/gut.51.4.562
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of primary sclerosing cholangitis and prognostic value of cholangiography in a Dutch population

Abstract: Background: Median survival of patients with primary sclerosing cholangitis (PSC) has been estimated to be 12 years. Cholangiography is the gold standard for diagnosis but is rarely used in estimating prognosis. Aims: To assess the natural history of Dutch PSC patients and to evaluate the prognostic value of a cholangiographic classification system. Patients: A total of 174 patients with established PSC attending a university hospital and three teaching hospitals from 1970 to 1999. Methods: Charts were reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
186
3
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(200 citation statements)
references
References 13 publications
6
186
3
5
Order By: Relevance
“…14 We included the control ERCP in the study protocol because classification and staging of cholangiographic abnormalities has been shown to have prognostic value. 44 In those patients in whom comparable examinations with adequate filling were available, a trend showing either improvement or no progression of the disease was seen in the UDCA/MTZ group compared with those on UDCA monotherapy. However, no differences were evident dur-ing 3 years of therapy between the groups regarding referrals for liver transplantation, progression to decompensated liver cirrhosis, development of malignancy, or death.…”
Section: Discussionmentioning
confidence: 99%
“…14 We included the control ERCP in the study protocol because classification and staging of cholangiographic abnormalities has been shown to have prognostic value. 44 In those patients in whom comparable examinations with adequate filling were available, a trend showing either improvement or no progression of the disease was seen in the UDCA/MTZ group compared with those on UDCA monotherapy. However, no differences were evident dur-ing 3 years of therapy between the groups regarding referrals for liver transplantation, progression to decompensated liver cirrhosis, development of malignancy, or death.…”
Section: Discussionmentioning
confidence: 99%
“…Typical changes seen in PSC consist of minor irregularities of duct contour and local narrowing with prestenotic dilatation (type I), threadlike narrowings alternating with normal caliber of bile ducts or slight dilatation (type II), multiple strictures with saccular dilatations (type III), and the most advanced changes consisting of advanced ductal narrowing with resultant lack of filling of the peripheral ducts (type IV). The classification has later been modified by Majojie et al (21) and Ponsioen et al (22,23). The classification of Ponsioen et al (23) has been validated and shown to correlate with patient prognosis 6 ( Table 2).…”
Section: Ductographic Criteria For Pscmentioning
confidence: 99%
“…Median survival from time of diagnosis to death or liver transplantation was reported as 10 years (Farrant et al, 1991). In a Dutch cohort, transplantation free survival was 18 years on average (Ponsioen et al,2002 ). PSC patients are prone to end stage liver disease complications such as esophageal varices, ascites, and hepatic encephalopathy.…”
Section: Natural Historymentioning
confidence: 99%